PROBLEMS IN SOCIO-ECONOMIC ANALYSIS OF DIGITAL INFRASTRUCTURE PROJECTS (International journal of artificial intelligence, 2026)
This article analyzes the main problems that arise in the process of assessing the socio-economic effectiveness of digital infrastructure projects. In the context of the rapid development of digital technologies, the assessment of infrastructure projects using traditional economic analysis methods has a number of limitations. The article highlights these limitations, including data gaps, difficulties in measuring intangible benefits, and the influence of institutional factors. It also puts forward scientific and practical proposals to overcome the problems.